Changing Me, Changing Us: Relationship Quality and Collective Efficacy as Major Outcomes in Systemic Couple Therapy. Issue 2 (28th June 2017) - Aguilar‐Raab, Corina; Grevenstein, Dennis; Gotthardt, Linda; Jarczok, Marc N.; Hunger, Christina; Ditzen, Beate; Schweitzer, Jochen
Abstract : We examine the sensitivity to change in the Evaluation of Social Systems (EVOS) scale, which assesses relationship quality and collective efficacy. In Study 1 we conducted a waitlist‐control, short‐term couple therapy RCT study ( N  =   43 couples) with five systemic therapy sessions treating communication and partnership problems; our intent was to provide high external validity. Construct validity of EVOS was assessed by comparison with additionally applied scales (Family Scales; Outcome Questionnaire, OQ‐45.2). In Study 2, N  =   332 individuals completed an experiment with high internal validity in order to verify sensitivity to change in three different social contexts. Results from Study 1 revealed a significant increase in relationship quality in the treatment group directly after treatment, as compared to the control group. Sensitivity to change was slightly better for EVOS than for other measures. While this positive change could not be fully sustained between posttreatment and a 4‐week follow‐up, EVOS score did not fall below baseline and pretreatment levels, supporting moderate‐to‐large sensitivity to change. Study 2 supported high sensitivity to change in EVOS for couple relations, family relations, and work‐team relationships. Therefore, EVOS can be used as an outcome measure to monitor the process of systemic interventions focusing on relationship quality and collective efficacy. Due to its sensitivity to change, EVOS can provide evidence for treatment success with regard to relationship aspects.